2019
DOI: 10.1103/physrevd.100.104047
|View full text |Cite
|
Sign up to set email alerts
|

Shortcomings of Shapiro delay-based tests of the equivalence principle on cosmological scales

Abstract: The "Shapiro delay" experienced by an astronomical messenger traveling through a gravitational field has been used to place constraints on possible deviations from the equivalence principle. The standard Shapiro delay used to obtain these constraints is not itself an observable in general relativity, but is rather obtained by comparing with a fiducial Euclidean distance. There is not a mapping between the constraints obtained in this manner and alternative theories that exhibit equivalence principle violations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 82 publications
3
38
0
Order By: Relevance
“…Eq. 6 is consistent (Minazzoli et al 2019b) up to at least ∼ 400 Mpc (𝑧 ∼ 0.1) when Shapiro Time Delay is calculated from observed galaxy clusters. Now, in this paper, we focus on a time lag under gravity between two photons with different energies.…”
Section: Theoretical Modelsupporting
confidence: 69%
See 2 more Smart Citations
“…Eq. 6 is consistent (Minazzoli et al 2019b) up to at least ∼ 400 Mpc (𝑧 ∼ 0.1) when Shapiro Time Delay is calculated from observed galaxy clusters. Now, in this paper, we focus on a time lag under gravity between two photons with different energies.…”
Section: Theoretical Modelsupporting
confidence: 69%
“…If both the violation of WEP and Δ𝑡 DM show an equivalent dependence on 𝜈 −2 obs , the two effects are not distinguishable (Ioka 2003;Macquart et al 2020;Inoue 2004). Until now, current studies of FRBs or any other sources have not found any such violation due to frequency (Einstein 1908;Tingay & Kaplan 2016;Nusser 2016;Minazzoli et al 2019a;Xing et al 2019).…”
Section: Theoretical Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…(36) uses an implicit coordinate system that is not gaugeinvariant, i.e., depending on the coordinate choice one can obtain positive or negative values (Gao and Wald 2000). In Minazzoli et al (2019) they consider Fermi coordinates associated to an observer, such that the delay is expressed in terms of an observed proper time, which results in a sum of terms with opposing sign. Using reasonable constructions for contributions to the total gravitational well experienced by propagating particles by considering the sum of catalogs they show the induced total (absolute) Shapiro delay is not monotonic, and indeed crosses zero in some cases.…”
Section: The Weak Equivalence Principlementioning
confidence: 99%
“…Therefore, while we can use the small offsets for, e.g., GW-GRBs to state that we find no evidence for WEP violation, we cannot quantify robust limits on relative Shapiro delay. Minazzoli et al (2019) suggest this as motivation for the development of tests for specific alternative theories of gravity. We note that if the WEP is violated we will find evidence for it, we will just be unable to quantify the degree of violation with this test.…”
Section: The Weak Equivalence Principlementioning
confidence: 99%